Лінгво-психологічна характеристика прикметників та проблема їх лексикографічного опису - Жуйкова, Маргарита; Zhuykova, Marharyta (My University, 2018)
In the semantics of many adjectives (words that characterize various properties of the objects) a significant place belongs to the features that a person perceives through the perception organs. A psycholinguistic experiment with Russian native-speakers has been conducted. Within this experiment a significant group of nouns (more than 7.6 thousand units), which are directly related to one or another sensation (hearing, sight, smell, taste or touch), has been discovered. To the respondents’ mind, about 100 adjectives among this group mark the features that a speaker perceives on touch (the temperature parameters of objects, texture of their surface, consistency, presence or absence of moisture, etc.). The purpose of our study was to identify correlations between the data obtained in the psycholinguistic experiment and the lexicographic description of the corresponding adjectives carried out by traditional linguistic techniques. We used information from various dictionaries of Russian language, complemented by data from lexicographic sources of English, Ukrainian, Polish, and Italian. Two groups of adjectives (adjectives with the semantics of temperature and adjectives with the semantics of texture of their surface) have been examined in details. The general conclusion is that lexicographers mostly ignore the mention of the channel of perceptual information, often using synonyms or internal references in interpretations. This makes the lexicographic description of the adjectives little informative, does not reflect the psycholinguistic reality, does not give an idea of the significant role that belongs to the perceptual component in the semantic capacity of adjectives. У семантиці багатьох прикметників – слів, що характеризують різні властивості предметів, значне місце належить ознакам, які людина отримує через органи сприйняття. У психолінгвістичному дослідженні, проведеному з носіями російської мови, була виявлена значна група іменників (більше ніж 7,6 тисяч одиниць), які безпосередньо пов’язані з тим чи тим відчуттям (слухом, зором, нюхом, смаком чи дотиком). Серед них близько 100 прикметників, на думку опитаних, називають такі ознаки, які мовці сприймають на дотик (температурні параметри предметів, фактура їхньої поверхні, консистенція, наявність чи відсутність вологи тощо). Мета нашого дослідження полягає у виявленні кореляцій між даними, які було отримано в психолінгвістичному експерименті, та лексикографічному описі відповідних прикметників, здійсненому традиційними лінгвістичними прийомами. Ми залучали інформацію переважно із різних словників російської мови, доповнюючи її даними із лексикографічних джерел англійської, української, польської та італійської мов. Докладно обстежено тлумачення прикметників двох груп: з семантикою температури та семантикою фактури поверхні. Загальний висновок полягає в тому, що лексикографи здебільшого ігнорують згадку про канал перцептивної інформації, часто використовуючи в тлумаченнях синоніми чи внутрішні відсилки. Це робить лексикографічний опис прик-метників малоінформативним, не відбиває психолінгвальної реальності, не дає уявлення про ту значну роль, яка належить перцептивному компоненту в семантичному на-вантаженні прикметників.
Linguistic and Psychological Features of Adjectives and Their Lexicographic Description Problem
Keywords: лексичне значення; психолінгвістичний експеримент; тлумачний словник; дефініція; перцептивна ознака; lexical meaning; psycholinguistic experiment; explanatory dictionary; definition; perceptual feature